445 - The factors associated with the presence of psychotic symptoms in the HELIAD Greek community study of older adults. (October 2020) - Vasiliadis, Helen-Maria; Gournelis, Rossettos; Efstathiou, Vassia; Stefanis, Nikos; Kosmidis, Mary H.; Yannakoulia, Mary; Dardiotis, Efthimios; Hadjigeorgiou, Georgios; Sakka, Paraskevi; Ntanasi, Eva; Pachi, Ioanna; Stefanis, Leonidas; et al.
ABSTRACT: Background: The prevalence and associated factors related to psychotic symptoms in older adults are understudied. The objectives were to assess the prevalence, incidence and factors associated with psychotic symptoms in a representative Greek sample of community living older adults. Methods: This study includes older adults aged ≥ 65 years participating in the Hellenic Longitudinal Investigation of Aging and Diet. The analysis is based on n=1, 904 participants with available data at baseline and n=947 participants at the 3-year follow-up. The presence of delusions and hallucinations in the past month was assessed on the grounds of the 17 symptoms of the Columbia University Scale for Psychopathology in Alzheimer's Disease and of the 14 symptoms of the Neuropsychiatric Inventory Questionnaire. An affirmative answer to any of these 31 symptoms defined the presence of psychotic symptoms. A comprehensive neuropsychological assessment for probable diagnosis of dementia and physical comorbidity was carried out by neurologists. Study factors included age, education, marital status, widowed in the past year, occupation, hearing impairment and number of chronic comorbidities. Penalized logistic regression analyses were carried out to assess the socio-demographic and clinical factors associated with the prevalence and incidence of psychotic symptoms. Results: The past-month prevalence of any psychotic symptom was 1.9% and 1.0% when excluding cases of dementia. The prevalence of any delusion and hallucination was 1.5% and 0.7%, and 0.8% and 0.3% when excluding cases with dementia. Paranoid delusions were the most prevalent. The incidence at the follow-up of any psychotic symptom was 2.1% and 1.3% when excluding dementia. Individuals not married had twice the odds and, farmers/breeders had three times the odds than public servants/teachers/executives of experiencing psychotic symptoms. Hearing impairment and the number of comorbidities increased the odds of the presence of psychotic symptoms. In addition to age and recent widowhood, these factors remained significantly associated with the presence of psychotic symptoms in cases without dementia. Conclusion: Dementia was not related to over half of the cases observed with psychotic symptoms. Paranoid delusions were the most prevalent. Socio-economic and health status factors are significant predictors of psychotic symptoms.